2021
DOI: 10.1002/aocs.12446
|View full text |Cite
|
Sign up to set email alerts
|

Combination of the Elevated Stearic Acid Trait with Other Fatty Acid Traits in Soybean

Abstract: Stearic acid is one of five major fatty acids found in soybean oil. It is a fully saturated lipid and is known for neutral or positive effects on LDL cholesterol when consumed by humans. Unfortunately, stearic acid only accounts for about 4% of the total seed oil produced in commodity soybean. Previous work has shown that stearic acid can reach levels as high as 28% of the total oil fraction when the SACPD‐C gene, encoding the delta‐9‐stearoyl‐acyl carrier protein desaturase responsible for most of the stearic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…For example, the down-regulated expression of two homologous FAD2 genes in peanut, based on the CRISPR/Cas9 method, resulted in increased oleic acid levels in stably transformed seeds, compared to the wild type [20]. Soybean seeds with SACPD-C and FAD2-1A mutant alleles showed stearic acid contents from 14% to 21%, while the oleic acid content was increased [25]. CRISPR/Cas9 was used to knock out the GmFATB1 gene, or one or both of them, to produce the mutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the down-regulated expression of two homologous FAD2 genes in peanut, based on the CRISPR/Cas9 method, resulted in increased oleic acid levels in stably transformed seeds, compared to the wild type [20]. Soybean seeds with SACPD-C and FAD2-1A mutant alleles showed stearic acid contents from 14% to 21%, while the oleic acid content was increased [25]. CRISPR/Cas9 was used to knock out the GmFATB1 gene, or one or both of them, to produce the mutant.…”
Section: Discussionmentioning
confidence: 99%
“…The soybean FAD2 gene is expressed differently in different plant tissues, which improves its ability to resist cold and salt stress by regulating the contents of diene fatty acids [20]. It has also been observed that combinations of polyvalent mutants do not seem to affect other agronomic characteristics, such as plant morphology and other quality traits [16,25]. In this study, various agronomic traits of plants of different genotypes were investigated and analyzed during the whole growth period, and it was found that the plant height of the JN38-mutant was significantly higher than that of receptor plants, which might be due to differences in varieties.…”
Section: Discussionmentioning
confidence: 99%